Attitudes and Recommendations of Physicians towards Alcohol Consumption and Cardiovascular Health: A Perspective from Argentina - Ricardo Lopez Santi; Sohaib Haseeb; Bryce Alexander; Adrian D′Ovidio; Sergio Gimenez; Carlos Secotaro; Diego Martinez Demaria; Luis Maria Pupi; Sonia Costantini; Daniel Piskorz; Alejandro Amarilla; Alberto Lorenzatti; et al. (Diseases, 2018)
Despite epidemiological findings of improvements in cardiovascular risk factors with a light-to-moderate intake of alcohol, many misconceptions remain regarding alcohol intake and the risks and benefits of consumption. We sought to examine physician attitudes and recommendations regarding alcohol intake in a cohort of Argentine physicians and to establish their sources of knowledge. An online national survey was distributed through the Argentine Federation of Cardiology (FAC) to cardiologists, internal medicine specialists, general and other subspecialty physicians in Argentina. The survey was completed by 745 physicians, of whom 671 (90%) were cardiologists. In total, 35% of physicians viewed moderate alcohol intake to be beneficial for cardiovascular health, 36% believed only wine offered such benefits, 24% viewed any intake to be harmful, and 5% had other opinions. More than half (57%) self-reported their knowledge came from academic sources. Regarding knowledge of drinking guidelines, only 41% of physicians were aware of the concept of “standard drink”. Physicians were generally not comfortable converting standard drinks into other metric units, however men tended to be more comfortable than women (p = 0.052). Physicians were not satisfied with their knowledge of drinking guidelines (3.01 ± 2.73, on a 0–10 scale). Physicians were generally comfortable in counselling patients regarding safe limits of consumption (6.22 ± 3.20, on a 0–10 scale). Argentine physicians were not satisfied with their knowledge of alcohol consumption guidelines or their understanding of the reported metrics. Only one-third of study participants viewed moderate alcohol intake as beneficial for cardiovascular health. This study shows the necessity to optimize the sources of knowledge.